A study on the effectiveness of promotion activities towards attracting more shoppers to star parade shopping center / Siti Munirah Abdul Manap - Abdul Manap, Siti Munirah (Faculty of Business and Management, 1998)
Not everybody knows what is shopping center. Most people will think that, it is a place that have many shops and have one or two big supermarket or departmental store or worst of all, many people think that shopping center is the departmental store or supermarket or hypermarket itself! Shopping center can be specifically defined as, "A group of architecturally unified commercial establishments built on a site which is planned, developed, owned and managed as an operating unit related in its location, size and type of shops of the trade area that the unit serves (Urban-Land lnstitute,1997,p.1).